Secrets to success for professionals in the autism field : an insider's guide to understanding the autism spectrum, the environment, and your role - Gerland, Gunilla (London : Jessica Kingsley Publishers, 2013)
Writing with the insight of someone on the autism spectrum, but also as an experienced autism professional, Gunilla Gerland offers a fresh and original perspective on autism as well as a wealth of new tools and interventions to use in practice with children and adults.
Includes bibliographical references and index.
Keywords: Autistic children -- Education; Autistic children -- Care; Autism spectrum disorders; Autistic people -- Rehabilitation